Sewing room accessories - Shore, Debbie (Writer on sewing) (Love to sew., 2017)
The latest addition to the Love to Sew series, this new title from best-selling author Debbie Shore contains 15 gorgeous, practical items that every sewer will love to make, use or give as gifts. The book contains storage solutions and sewing accessories to equip every sewing space. The projects range from practical storage solutions such as tool rolls, carry cases and cutting mat carriers to innovative ways to keep a sewing space tidy, such as a handy armchair storage device and an ironing station, complete with board cover and handy hanging pouch for storing a mini iron and attachments. The book also contains colourful sewing room essentials such as a pincushion, a seam press and handmade bobbins, and inspiring items perfect to give as gifts: a sewing room diary cover and a sewing case. The book contains a comprehensive materials and techniques section at the beginning, showing clearly all the techniques needed, with beautiful photography and easy-to-follow instructions. Each of the projects contains step-by-step photography and clear instructions so that even beginners will find these projects a doddle.